2016
DOI: 10.1590/s1806-92902016000400005
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical response to Omega-3 plus as a dietary supplement to growing goats under hot summer conditions

Abstract: -The objective of the present study was to assess the effect of dietary supplementation of Omega-3 plus on some the physiological and biochemical traits in growing Baladi goats under hot summer conditions. Thirty-four growing male goats (4-5 months old) were randomly divided into two equal groups. Animals in group 1 were fed a concentrate feed mixture (CFM), which was the control group. Goats in group 2 (the experimental group) were offered Omega-3 plus (1,000 mg/animal day -1 ) (30% fish oil, containing 18% e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
2
5
1
Order By: Relevance
“…Cholesterol levels of ram lambs were the highest level (P≤0.05) in control (70 mg/dL) followed by T1 (69.17 mg/dL) and T2 (68.11 mg/dL). The increases in concentrations of plasma protein and albumin due to fish oil is in agreement with previous results reported by Teama and El-Tarabany (2016) who found that total protein levels are significantly increased as a result of supplementation of omega-3 plus in the diet of goats. No differences were detected for total globulin, which was in accordance with the report of (Kholif et al, 2016) and A/G ratio, with (Abu El-Hamd et al, 2015).…”
Section: Effect Of Dietary Fish Oil Supplementation On Blood Constitu...supporting
confidence: 92%
See 1 more Smart Citation
“…Cholesterol levels of ram lambs were the highest level (P≤0.05) in control (70 mg/dL) followed by T1 (69.17 mg/dL) and T2 (68.11 mg/dL). The increases in concentrations of plasma protein and albumin due to fish oil is in agreement with previous results reported by Teama and El-Tarabany (2016) who found that total protein levels are significantly increased as a result of supplementation of omega-3 plus in the diet of goats. No differences were detected for total globulin, which was in accordance with the report of (Kholif et al, 2016) and A/G ratio, with (Abu El-Hamd et al, 2015).…”
Section: Effect Of Dietary Fish Oil Supplementation On Blood Constitu...supporting
confidence: 92%
“…The unaffected plasma triglyceride in this study was consistent with the report of Li et al (2012) in goats. In contrast, oil supplementation caused an increase in the concentration triglyceride in goats (Teama and El-Tarabany, 2016).…”
Section: Effect Of Dietary Fish Oil Supplementation On Blood Constitu...mentioning
confidence: 82%
“…Though, alteration among bucks treated groups was statistically nonsignificant in respect of serum tri-iodothyronine this result is harmony with Abdalla et al (2015) who reported that supplementation of 15% olive pomace concentration significantly (P<0.01) increased T3 concentration (40.80%) in goat compared to control group during hot summer. The results were inconsistent with that of Teama et al (2016) who reported significantly higher level of T3 hormones in goat that was fed with omega-3 plus, 30% fish oil, during warm summer for total duration of 4 months during hot summer.…”
Section: Table 1 Serum Biochemical Metabolites and Hormonal Profile contrasting
confidence: 92%
“…Other authors have shown that DHA dietary supplementation has a stimulatory effect on IgG and IgM production in rat splenocytes (both immunoglobulins) and mesenteric lymph node (only IgG) with no effect on IgA production (Hung et al, 1999). Also in goats, supplementation with mixtures of n-3 acids (mainly EPA and DHA) resulted in increased IgG serum concentration (Teama and El-Tarabany, 2016). In the study on calves fed MR supplemented with fish oil, only secondary IgG humoral response to ovalbumin was affected with no influence on the primary response (Ballou and De Peters, 2008).…”
Section: Discussionmentioning
confidence: 97%